Millennial attitudes towards sharing mobile phone location data with health agencies: a qualitative study. Issue 15 (18th November 2021) - Murphy, Hannah; Keahey, Lauren; Bennett, Emma; Drake, Archie; Brooks, Samantha K.; Rubin, G. James
ABSTRACT: The use of mobile phone devices leaves digital traces which include personal data of the user's location and can be used to produce aggregated and anonymised location data. There is widespread interest in utilising different types of mobile phone location data to optimise emergency health responses within a range of settings, however until now there has been no qualitative research exploring public opinions on sharing such data. A qualitative study with 40 millennials (born between 1981–2000) across six focus groups were conducted before and after widespread news reports about the leaking of personal data on social media and a major public health incident in the UK. Thematic analysis was used to identify themes in the data. Analysis identified four main themes and five subthemes suggesting the main concepts related to attitudes and concerns were 'Control', 'Trust', 'Risks to sharing' and 'Pros and cons of data sharing'. Millennials were generally accepting of sharing different types of location data with ambulance services and a public health agency if they were able to give explicit consent and retain some personal control towards how their data would be used. The results suggest that policymakers who wish to use aggregated and anonymized mobile phone location data to improve healthcare services should focus on reassurance about how data will be used and promoting public trust.